2013
DOI: 10.1186/1471-2296-14-189
|View full text |Cite
|
Sign up to set email alerts
|

Are patients’ preferences regarding the place of treatment heard and addressed at the point of referral: an exploratory study based on observations of GP-patient consultations

Abstract: BackgroundToday, in several north-western European countries, patients are encouraged to choose, actively, a healthcare provider. However, patients often visit the provider that is recommended by their general practitioner (GP). The introduction of patient choice requires GPs to support patients to be involved, actively, in the choice of a healthcare provider. We aim to investigate whether policy on patient choice is reflected in practice, i.e. what the role of the patient is in their choices of healthcare pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
3
12
0
1
Order By: Relevance
“…In a study examining acute illness in Switzerland, 66% of patients preferred physician decision-making 32. Previous studies demonstrated that factors affecting patients’ preferences in decision-making included the type of disease,29,33,34 the purpose of diagnosis or treatment of the disease,35 the relationship with professionals, the type of decision-making, the experience of care, and demographic characteristics 36. In this study, the rate of SDM was lower than that of studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining acute illness in Switzerland, 66% of patients preferred physician decision-making 32. Previous studies demonstrated that factors affecting patients’ preferences in decision-making included the type of disease,29,33,34 the purpose of diagnosis or treatment of the disease,35 the relationship with professionals, the type of decision-making, the experience of care, and demographic characteristics 36. In this study, the rate of SDM was lower than that of studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2007 and 2008, a study carried out in the Netherlands showed that patients who were referred for diagnostic purposes had less involvement in choosing their healthcare provider than those who were referred for treatment. 11 …”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands and many other Western-European countries such as Denmark, Norway, Sweden, and the United Kingdom, family physicians usually serve as gatekeepers to specialist medical care. The family physician also traditionally chooses the medical specialist provider, usually without much involvement from patients themselves (Earwicker & Whynes, 1998;Victoor et al, 2013;Vrangbaek, Østergren, Birk, & Winblad, 2007). Since the late 1990s, health care reforms have been gradually introduced in the Netherlands and most other Western-European countries that aim to facilitate increased competition between health care providers (Helderman, Schut, van der Grinten, & van de Ven, 2005;Martinsen & Vrangbaek, 2008).…”
Section: Context Of the Present Studymentioning
confidence: 99%
“…In line with common consultation room practices (Couët et al, 2013), the family physician would initiate a referral. Also in line with existing practices in Western European countries (Victoor et al, 2013;Vrangbaek et al, 2007), referral would be to a specialist at a nearby general hospital. Participants were asked to indicate their most likely reaction, with a choice between: (a) visiting the specialist at the general hospital without asking the family physician any questions about the private specialist provider, or (b) asking the family physician questions about referral to the private specialist provider.…”
Section: Intention To Question Physician Gatekeeper's Referralmentioning
confidence: 99%